#### Question

If `(5x + 6y)/(5u + 6v) = (5x - 6y)/(5u - 6v)` then prove that x : y = u : v

#### Solution

`(5x + 6y)/(5u + 6v) = (5x - 6y)/(5u - 6v)` (By aletrnendo)

`(5x + 6y)/(5x - 6y) = (5u + 6v)/(5u - 6v)`

`(5x + 6y + 5x - 6y)/(5x + 6y - 5x + 6y) = (5u + 6v + 5u - 6v)/(5u + 6v - 5u = 6v)` (By componendo and dividendo)

`(10x)/(12y) = (10u)/(12v)`

`x/y = u/v`

Is there an error in this question or solution?

Advertisement

Advertisement

If `(5x + 6y)/(5u + 6v) = (5x - 6y)/(5u - 6v)` Then Prove that X : Y = U : V Concept: Componendo and Dividendo Properties.

Advertisement